Narration, Genre, and Pseudonymity: Reconsidering the Individuality and the Literary Relationship of the Pastoral Epistles - Herzer, Jens (Journal for the study of Paul and his letters, 2019)
In the last two decades, the classical paradigm of the literary unity of the Pastoral Epistles as a three-part "Corpus Pastorale" has been challenged and defended in various ways. The discussion has accompanied a new discourse on pseudonymity and its relevance for New Testament writings. This article traces the development of the hypothesis of the Pastoral Epistles' pseudonymity and illuminates the problems this hypothesis entails. Focusing on narrative elements and genre (such as mandata or ancient letter novel), individual traits of each letter will be discussed exemplarily in order to reconsider their relationship. Highlighting the letters' individual profiles leads to a more refined interpretation beyond the old controversy between authenticity and pseudonymity. As a result (which cannot be a substantial part of this article), Titus and 2 Timothy can be interpreted as authentic letters of Paul, written in his last years, whereas 1 Timothy is best situated in the anti-heretic struggles of the second century AD.